We Shall Be Masters : Russian Pivots to East Asia from Peter the Great to Putin - Miller, Chris (London Harvard University Press, 2021)
Generations of Russians have pursued wealth and power in the East, colonizing Pacific regions and spreading political influence into Asia. Why have these efforts largely failed? Chris Miller argues that Russian citizens and leaders, concentrated in the European borderlands, have always struggled to maintain faith and interest in eastward expansion.
Include Map and Index
Keywords: Russia -- Soviet Union -- America -- Asia -- Russia (Federation) -- International relations